Pembangunan Sistem Informasi Berbasis Web Direktori Pariwisata Menggunakan Arsitektur REST API di Badan Pusat Statistik - Syibli, Muhammad; Ridho, Farid (Seminar Nasional Official Statistics, 2023)
Indonesia has a large potential tourism industry so the government needs to promote it well through technology-based tourism information management. In addition, there is a need for a forum to disseminate the results of tourism information management to the community by integrating it with the Webentry and Wilkerstat systems. Based on this, it is necessary to build a web-based tourism directory system at BPS. The design of the system interface uses the card sorting method to organize the layout of features based on the principle of visual and information hierarchy. Then, there is the use of Representational State Transfer Application Programming Interface (REST API) to implement public information disclosure. Then, the tourism directory system is built using a three-tier client-server architecture with the CodeIgniter 3 framework and Bootstrap 4. The system development method used is the Software Development Life Cycle (SDLC) waterfall model. After the system development stage is complete, it is necessary to test the features using the black box testing method and the results are as expected. Furthermore, there is a system usability test using the System Usability Scale (SUS) survey with a final score of 80.17 or good category.